(3GddhGeY GdEdgjI aj GdeHGMK GdcdGejIs - (3ebOGO Hf YHO Gddg Hf eMeO Hf GdMSjf Hf eMeO GdSjhQj GdMdj GdCSOj,J (B826 (3g` s ((3eMeO Hf WGgQ GdSeGhi s)
(3ChdgG (B:s
(3hHYO adeG JWGHb GdYbd hGdfbd hJhGab GdaQY hGdCUd Ydi YXe GdYde hLdGdJg bOQkG hGQJaGY Cgdg s
(3BNQgG (B:s
(3eef jba Ydi gPG GdcJGH Cf jUdM bO Je cJGH GddhGeY GdEdgjI ai GdeHGMK GdcdGejI s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B282 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B318s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B413s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds